Product Design and Process Design That Influence the Quality of Shirt Products - Haryadi, Dudi; Fauzan, Ilham (Almana : Jurnal Manajemen dan Bisnis, 2025)
Clothing is no longer just a common thing, but also requires aesthetics and attractive designs that can increase the wearer's confidence. Along with the development of the times, people are increasingly selective in choosing products. The clothing industry must take advantage of this opportunity by continuing to innovate in creating new, unique and high-quality clothing models, in order to meet market needs and compete well. This study aims to measure the level of product quality produced due to the influence of Product Design and Process Design on the Quality of Shirt Products at PT.Nirwana Indo Apparell. This research was conducted with a quantitative approach. The methods applied are descriptive and verification analysis. Data were collected through company data, literature studies and distributing questionnaires to 60 respondents and their calculations using the SPSS 26 program. Data analysis was carried out using the path analysis method. Based on the results of the study, it was found that product design is included in the fairly good category, process design is included in the fairly good category, and product quality is also included in the fairly good category. In addition, Product Design also has an influence on product quality, as well as process design which affects product quality. Overall, product design and process design simultaneously affect product quality.